New Teachers Identify Teacher Leaders as Key Support for Transition into the Profession - Brown, Barbara; Friesen, Sharon (International Journal of Education Policy and Leadership, 2025)
Through an analysis of 289 open-ended survey responses, this study examines how teacher leaders support new teachers transitioning from teacher preparation programs to full-time teaching positions. An analysis of the responses revealed that teacher leaders support new teachers with instructional planning, professional learning, mentorship, resource sharing, assessment guidance, and inclusive teaching strategies. Through these efforts, teacher leaders foster collaborative and reflective practices, cultivate professional capital, and promote adaptive expertise. The findings emphasize the relational nature of teacher leadership, highlighting the role of teacher leaders in co-constructing professional growth and resilience among new teachers and enhancing teacher development. Implications for policy and practice include prioritizing teacher leadership initiatives to reduce new teacher attrition, promote equity, and foster sustainable professional cultures within schools.